2017
DOI: 10.1186/s13020-016-0122-9
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture for the prevention of postoperative gastrointestinal dysfunction in participants undergoing vascular laparotomy under general anesthesia: a randomized controlled trial

Abstract: BackgroundPostoperative gastrointestinal dysfunction (PGD) is a common complication following laparotomy under general anesthesia (GA). Abdominal distension occurs in 8–28% of surgeries within 24 h postoperatively. The present study aimed to analyze the efficacy of electroacupuncture (EA) for the prevention of PGD by applying preoperative EA stimulation of PC6 (Neiguan), ST36 (Zusanli), and ST37 (Shangjuxv) bilaterally twice within 24 h prior to surgery, compared with no acupuncture treatment.MethodsThe study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Preoperative EA at neiguan (PC6), ST36, and ST37 might be useful for preventing postoperative gastrointestinal dysfunction, thereby improving gastrointestinal function recovery. [ 32 ] In our study, ST36-ST37 were only selected and we found that EA at ST36-ST37 not only attenuated inflammatory responses but also reduced IAP. Therefore, EA at ST36-ST37 is convenient, effective, and feasible in ICU.…”
Section: Discussionmentioning
confidence: 82%
“…Preoperative EA at neiguan (PC6), ST36, and ST37 might be useful for preventing postoperative gastrointestinal dysfunction, thereby improving gastrointestinal function recovery. [ 32 ] In our study, ST36-ST37 were only selected and we found that EA at ST36-ST37 not only attenuated inflammatory responses but also reduced IAP. Therefore, EA at ST36-ST37 is convenient, effective, and feasible in ICU.…”
Section: Discussionmentioning
confidence: 82%
“…Some RCTs [20,[27][28] have shown that EA on these acupoints can shorten the time of first flatus and defecation and can reduce the length of hospital stay. However, the number of cases in these studies is small, and the quality of research is not high.…”
Section: Discussionmentioning
confidence: 99%
“…Similar outcomes have been applied in previous studies on gastrointestinal dysfunction, such as the time to the first passage of flatus, the time of the first defecation, visual analogue scale (VAS), quality of life [4,18] , and the length of hospital stay [19][20][21] . Thus, we will adopt these outcomes in this study due to their wide application.…”
Section: Outcome Measures {12}mentioning
confidence: 99%
“… [56] A randomized, controlled, clinical trial confirmed that in the liver and vascular surgery, electroacupuncture at Zusanli and Xiaxu preoperatively was significantly improved in postoperative first ventilation, defecation, and hospital stay. [57] It was found that electroacupuncture at Zusanli could effectively improve postoperative intestinal obstruction and shorten the recovery time by measuring the intestinal motility, c-kit and P2X7 mRNA levels of rats at different time points during the modeling, which may be related to the increase of the content of mesenchymal cells in the intestinal myenteric plexus. [58] The effect of acupuncture at Sanyinjiao, Zusanli, Shuidao, and Shenque on day 15 after radical hysterectomy on postoperative urinary retention was assessed.…”
Section: Application and Benefit Of Acupuncture In Perioperative Perimentioning
confidence: 99%